2022
DOI: 10.1161/atvbaha.122.318314
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Landscapes of Nondiseased Human Cardiac Valves From End-Stage Heart Failure–Explanted Heart

Abstract: Background: Exploring the mechanisms of valvular heart disease at the cellular level may be useful to identify new therapeutic targets; however, the comprehensive cellular landscape of nondiseased human cardiac valve leaflets remains unclear. Methods: The cellular landscapes of nondiseased human cardiac valve leaflets (5 aortic valves, 5 pulmonary valves, 5 tricuspid valves, and 3 mitral valves) from end-stage heart failure patients undergoing heart tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 96 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Although not directly focused on CAVD pathogenesis, the comparative study of distinct cellular compositions of 18 nondiseased human aortic, pulmonary, tricuspid, and mitral valves from end-stage heart failure patients has provided a baseline for valvular heterogeneity and shed light on left/right-side differences in leaflet composition, mechanobiological regulation of VIC phenotypes, and disease susceptibility of the AV. 39 Xu et al 15 reported the first scRNA-seq study of adult human CAVD, where they sequenced 34 632 cells from 6 donors after mechanical dissociation and enzymatic digestion. Their analyses identified subsets of VICs, VECs, macrophages, and lymphocytes.…”
Section: Single-cell Omics Strategies and The Study Of Valvular Heter...mentioning
confidence: 99%
“…Although not directly focused on CAVD pathogenesis, the comparative study of distinct cellular compositions of 18 nondiseased human aortic, pulmonary, tricuspid, and mitral valves from end-stage heart failure patients has provided a baseline for valvular heterogeneity and shed light on left/right-side differences in leaflet composition, mechanobiological regulation of VIC phenotypes, and disease susceptibility of the AV. 39 Xu et al 15 reported the first scRNA-seq study of adult human CAVD, where they sequenced 34 632 cells from 6 donors after mechanical dissociation and enzymatic digestion. Their analyses identified subsets of VICs, VECs, macrophages, and lymphocytes.…”
Section: Single-cell Omics Strategies and The Study Of Valvular Heter...mentioning
confidence: 99%
“…These results could potentially explain important sex-differences in myocardial infarction observed in clinical practice 34 . Like the four chambers, the four cardiac valves were also shown to have distinct cellular composition: migratory valvular interstitial cells (VIC), mast cells, myo broblasts, and shear stress-reactive valvular endothelial cells (VEC) were found in aortic valve; shear stress-reactive VEC and mast cells were in pulmonary valve; nitric oxide (NO)-associated VIC, protective VEC, and migratory anti-in ammatory T cells were found in tricuspid vale; and mast cells and myo broblasts were in mitral valve 35 . Other specialised subdomains such as sinoatrial node (SAN) have also been studied at single cell level: a study of 718 SAN cells from 21 adult mice has identi ed Vsnl1 as a potential sinoatrial node marker and de ned four distinct transcriptional cluster 36 .…”
Section: Heterogeneity In the Healthy And Diseased Heartsmentioning
confidence: 99%
“…Emerging studies at a single-cell level revealed molecular heterogeneity among valvular endothelial cells. [10][11][12][13] Importantly, these studies identified genes, such as transcription factor Prox1, marking diverse subpopulations within valvular endothelial cells lining cardiac valves. 13 These findings suggest Prox1, thought to be expressed specifically in lymphatic and venous valve endothelium, [14][15][16] as components of shared common pathways driving multisystem valvular defects.…”
Section: Article See P 463mentioning
confidence: 99%